Growth of Carbon Nanotubes inside Boron Nitride Nanotubes by Coalescence of Fullerenes: Toward the World's Smallest Coaxial Cable. Issue 9 (13th July 2017) - Walker, Kate E.; Rance, Graham A.; Pekker, Áron; Tóháti, Hajnalka M.; Fay, Michael W.; Lodge, Rhys W.; Stoppiello, Craig T.; Kamarás, Katalin; Khlobystov, Andrei N.
Abstract : The use of boron nitride nanotubes as effective nanoscale containers for the confinement and thermal transformations of molecules of C60 ‐fullerene is demonstrated. The gas‐phase insertion of fullerenes into the internal channel of boron nitride nanotubes yields quasi‐1D arrays, with packing arrangements of the guest fullerenes different from those in the bulk crystal and critically dependent on the internal diameter of the host nanotube. Interestingly, the confined fullerene molecules: i) exhibit dynamic behavior and temperature‐dependent phase transitions analogous to that observed in the bulk crystal, and ii) can be effectively removed from within the internal channel of nanotubes by excessive sonication in organic solvent, indicating weak host–guest interactions. The thermal treatment of fullerenes confined within nanotubes at 1200 °C in argon triggers the polymerization and coalescence of the guest fullerenes into carbon nanotubes inside boron nitride nanotubes affording a hybrid nanostructure—the world's smallest coaxial cable—on a preparative scale, as confirmed by high‐resolution bright‐field transmission electron microscopy imaging, electron‐energy‐loss spectroscopy, energy‐filtered transmission electron microscopy elemental mapping, and UV–vis absorption spectroscopy. Abstract : A new route toward the preparative scale formation of the world's smallest coaxial cable, comprising an electrically conducting carbon nanotube inside an insulating boron nitride nanotube, is described utilizing the selective confinement and thermally initiated transformation of molecules of C60 ‐fullerene inside boron nitride nanotube nanoreactors.